2019
DOI: 10.1158/1078-0432.ccr-19-0152
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Residual Disease and Adjuvant Trial Design in Solid Tumors

Abstract: Advances in diagnosis and treatment have resulted in a high rate of survival for many patients with early-stage cancers. However, identifying who is at ongoing risk of relapse remains of high priority to direct subsequent adjuvant therapy. Multiple recent retrospective studies have shown that detection of tumor-derived materials in blood, in particular with circulating tumor DNA (ctDNA) analysis, can identify patients with residual disease before clinical or radiological evidence of metastatic disease, anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 72 publications
1
46
0
Order By: Relevance
“…[12][13][14][15][16] Prospective trials have now been initiated to explore how ctDNA status could optimally inform adjuvant therapy decision-making and ultimately improve patient outcomes. 17 Future prospective studies might be informed by consolidating lessons learnt from completed nonrandomized studies. Important questions include those about the optimal timing of blood collection after surgery, whether quantitative measurement of ctDNA mutation burden can provide further risk stratification when ctDNA is detectable, the predictive performance of ctDNA compared to known clinicopathologic risk factors, the impact of ctDNA mutation burden on…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16] Prospective trials have now been initiated to explore how ctDNA status could optimally inform adjuvant therapy decision-making and ultimately improve patient outcomes. 17 Future prospective studies might be informed by consolidating lessons learnt from completed nonrandomized studies. Important questions include those about the optimal timing of blood collection after surgery, whether quantitative measurement of ctDNA mutation burden can provide further risk stratification when ctDNA is detectable, the predictive performance of ctDNA compared to known clinicopathologic risk factors, the impact of ctDNA mutation burden on…”
Section: Introductionmentioning
confidence: 99%
“…This promise has been further demonstrated in nonmetastatic CRC 8‐11 and many other solid tumor types 12‐16 . Prospective trials have now been initiated to explore how ctDNA status could optimally inform adjuvant therapy decision‐making and ultimately improve patient outcomes 17 …”
Section: Introductionmentioning
confidence: 99%
“…2). Such an approach is not dissimilar from ongoing studies of minimal residual disease in which ctDNA‐positive patients receive ongoing therapy whereas ctDNA‐negative patients are permitted a treatment break 136 …”
Section: Risk Stratification Response Assessment and Resistance Monmentioning
confidence: 99%
“…The majority of the studies on solid tumors have been conducted with the specific aim of detecting molecular residual disease (MRD) after the completion of definitive therapy. This technique was applied successfully for MRD detection in several solid tumors, including colorectal cancer, breast cancer, lung carcinoma, pancreatic carcinoma, and nasopharyngeal carcinoma [22].…”
Section: Mrd In Solid Tumorsmentioning
confidence: 99%
“…The pioneering study by Diehl et al demonstrated the feasibility of ctDNA detection in a significant cohort of cancer patients [22]. The study also demonstrated that ctDNA in the plasma has a short half-life (of <2 h), although the ctDNA levels may be elevated 24 h following surgical tumor resection, apparently due to the release of ctDNA from the damaged tissue [23].…”
Section: Mrd In Solid Tumorsmentioning
confidence: 99%